Online Learning: The Widespread Use of Google Forms as a Learning Media for Students in the Midst of the Covid-19 Pandemic - Adi Gunawan; Imam Tabroni; Dede Supendi (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
The purpose of this study was to determine the use of google form media and its effect on the effectiveness of online fiqh learning at MTs Al-Hidayah during the Covid-19 pandemic. The research uses a quantitative approach with a correlational design. Data collection techniques by distributing questionnaires (questionnaires) Variable X and Y to class VIII MTs Al-Hidayah as many as 68 samples. Based on the results of data analysis, it was concluded that first, the use of google form media was considered good with an average score of 80.66%. Second, the effectiveness of online learning is considered good with an average score of 80.27. Third, there is a significant effect between the use of google form media and the effectiveness of online learning with a correlation value of 0.823 which can be categorized as a very strong correlation. The determination value of 0.673 means that the influence of the X variable with the Y variable is 67.3% and the remaining 32.7% is influenced by other factors besides the use of google form media. With the regression equation Y = 14.056 + 0.771X, it means that if there is an increase in the X variable, it will also affect the Y variable.